Characteristics of the dairy farmers who perform financial management in Paraná State, Brazil - Roney Zimpel; Ferenc Istvan Bánkuti; Maximiliane Alavarse Zambom; Kellen Cristina Kuwahara; Sandra Mara Schiavi Bánkuti (Revista Brasileira de Zootecnia)
ABSTRACT The objective of this paper was to analyze financial management practices in dairy production systems. More specifically, we sought to identify which milk producers adopt financial management practices. We conducted 55 semi-structured questionnaires in the Western Region of Paraná. The data were processed through descriptive and multivariate statistical analysis. The analysis of hierarchical clusters defined, based on variables related to financial management practices, two distinct groups. The first group included milk producers who do not adopt financial management practices (N = 49) and the second group described the milk producers who do adopt these practices (N = 6). We then used Common Factor Analysis, along with structural, technical, productive, and socioeconomic variables to define the three factors that best explained the variance between the clusters: factor 1 - structural; factor 2 - social; factor 3 - informational. Smaller dairy production systems, with lower production, managed by younger producers, and employing younger workers, are those adopting financial management practices. Therefore, the scarcity of resources is not a limiting factor in the adoption of financial management practices.